Administration of bovine casein-derived peptide prevents cognitive decline in Alzheimer disease model mice. - Li-Juan Min; Yodai Kobayashi; Masaki Mogi; Kana Tsukuda; Akio Yamada; Koji Yamauchi; Fumiaki Abe; Jun Iwanami; Jin-Zhong Xiao; Masatsugu Horiuchi (PLoS ONE)
There is a growing interest in identifying natural food ingredients that may serve to prevent dementia such as that due to Alzheimer disease (AD). Peptides derived from food proteins have been demonstrated to have various physiological activities such as a hypotensive action. Recent findings have indicated possible associations of hypertension with AD progression, and suggest that angiotensin converting enzyme (ACE) inhibitors with potential to pass through the blood brain barrier (BBB) may reduce the risk of AD. In this study, we investigated the effect of milk peptide (CH-3) on cognitive function in AD model mice. CH-3 contains a tripeptide (methionine-lysine-proline, MKP) that has been found to have a strong ACE inhibitory effect and the potential to pass through the BBB. Adult male ddY mice were used in this study, and an animal model of AD was induced by intracerebroventricular (ICV) injection of Aβ1-42. CH-3 (250 mg/kg/day) or MKP (0.5 mg/kg/day) was orally administered every day starting 2 days before ICV injection. At 3 weeks after ICV injection, cognitive function was evaluated by the Morris water maze test. Brain samples were obtained after behavioral testing, and expression of inflammatory cytokines and NADPH oxidase subunits was measured by real-time quantitative RT-PCR. ICV injection of Aβ1-42 significantly impaired cognitive function compared with that in PBS-injected mice. Daily administration of CH-3 markedly attenuated this Aβ1-42-induced cognitive decline. Aβ1-42 injection significantly enhanced the expression of tumor necrosis factor-α (TNF-α), inducible nitric oxide synthase (iNOS) and p22phox in the mouse hippocampus compared with PBS injection, and showed a tendency to increase the expression of monocyte chemoattractant protein-1 (MCP-1), p47phox and gp91phox, whereas CH-3 treatment markedly reduced Aβ1-42-induced TNF-α, MCP-1, iNOS, p47phox and gp91phox expression. Finally, administration of MKP also attenuated Aβ1-42-induced cognitive impairment with an increase in cerebral blood flow. The present study demonstrated that repeated oral administration of CH-3 to AD model mice not only improved cognitive function but also suppressed the expression of inflammatory cytokines and production of oxidative stress, and suggests its therapeutic potential for preventing cognitive impairment in AD.